Conservation Systems to Enhance Soil Carbon Sequestration in the Southeast U.S. Coastal Plain. Issue 5 (20th September 2013) - Balkcom, Kipling S.; Arriaga, Francisco J.; van Santen, Edzard
Abstract : Tillage systems that promote minimal surface disturbance combined with high residue cover crops can sequester C, but additional research to quantify carbon sequestration with conservation agricultural systems is needed for modelers, policymakers, and landowners. A factorial arrangement of conservation tillage (no‐till, fall paratill, spring paratill, and spring strip‐till) and winter cover crops (no cover, rye [ Secale cereale L.], and wheat [ Triticum aestivum L.]) were established in a corn/cotton ( Zea mays L./ Gossypium hirsutum L.) rotation from 2004 to 2009 to (i) evaluate cover crop biomass production and associated changes in soil organic carbon (SOC) to 15 cm, (ii) evaluate the potential of conservation systems to sequester SOC after years of conventional tillage, and (iii) compare measured changes in SOC to predicted soil conditioning index (SCI) values. Carbon returned to the soil each year averaged 2500 and 1340 kg C ha –1 for cover crops and corn residue, respectively. The average SOC sequestration rate in the top 15 cm was 926 ± 344 kg C ha –1 yr –1 . Soil organic C values measured after 6 yr related well with predicted SCI values ( r 2 = 0.81; P = 0.0004). However, discrepancies between SCI and SOC values for conservation systems highlighted the need to improve the SCI for the Southeast U.S. Conservation systems following years of conventional monocropping were equivalent in their ability to sequester considerable amounts of C that will improve soil quality in the Coastal Plain of the southeastern USA.